Rural extension and associativism: the case of rural producers in Santana do Ipanema / AL Brazil / Extensão rural e associativismo: o caso dos produtores rurais em Santana do Ipanema/AL - Risoneide Pereira Nunes; João Paulo Silvério da Silva; Conceição Maria Dias de Lima (Universidade Estadual de Alagoas, 2017)
Agriculture extension and associative management have an important role of innovation to local development. The associative organizations represent an alternative to build this model of development, it able to show solutions to community social and economic problems. The aim is show relative information to small farmers of milk production and the work done together to Association of São Felix. The qualitative methods approach was structured with milk producers' organization through research-action method (THIOLLENT, 2011). Initially, it was fulfilled a exploratory research to select the producers´ organization to be studied. We collected information on the profile of members (gender, age, education, income and economic activities) and on history and functioning of the association (economic activity, courses, challenges, technical assistance, improvements, future projects) and training demands. They were developed three training on the topics: Alternative Food, Milking Management and hay production. The training was intended to approximate the technical information with the reality experienced by producers, as well as promoting university exchanges with the inserted community. It can be seen that the proposed research has social relevance, since it is a focused action research for the analysis of a local reality, where the population and its dynamism are the fundamental basis for the implementation of the actions of this work.